APPLICATION OF ARTIFICIAL INTELLIGENCE IN MODERN EDUCATIONТ - Vishnyakova , E.A. (Scientific practical conference, 2025)
The introduction of digital technologies into the educational process not only expands access to educational resources, but also opens up new opportunities for personalizing learning, increasing its effectiveness and adapting it to the individual needs of students. One of the most promising areas of digitalization of education is the use of artificial intelligence technologies.